(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
Background/purpose: The tubularized incised plate urethroplasty (Snodgrass technique) presents the procedure of choice for distal hypospadias repair. Fistula formation is the most common complication with various rates. Avoiding overlap of suture lines in the Snodgrass repair is critical to minimize fistula formation through second-layer coverage of the neourethra. We compared the outcome of double- layer dartos flaps to flapless procedure in the tubularized incised plate urethroplasty for distal hypospadias repair to assess the effectiveness of dartos flap in this method. Methods: Our study included 28 patients aged upto 12 years who were treated with tubularized incised plate urethroplasty for distal hypospadias in Shaheed Suhrawardy Medical College Hospital from April 2010 to December 2011. They were divided into two groups. Group A (14 patients) had double dartos flap coverings. Group B (14 patients) had no dartos flap covering. The dissected dorsal dartos flap was bisected vertically to form two pedicle wings. Each wing was rotated laterally from either side of the glans to cover the neourethra ventrally in a double-layer fashion. Result: Mean follow up period was 9 months. In Group A, one patient (7%) developed fistula and one (7%) superficial skin necrosis. On the other hand three (21%) patients developed fistula and one patient (7%) meatal stenosis in group B, who were treated with Snodgrass procedure without using dartos flap. All successful repaired hypospadias patients of both groups had a cosmetically normal looking circumcised penis with ventrally slit meatus. Conclusions : Double dartos flaps covering of the neourethra is a simple procedure and could be effective for the prevention of urethrocutaneous fistula after tubularized incised plate urethroplasty. J. Paediatr. Surg. Bangladesh 3(2): 65-70, 2012 (July)